Clinical profile of childhood epilepsy in Nigerian children seen in a tertiary hospital - Eyong, Komomo Ibor; Ekanem, Emmanuel E.; Asindi, Asindi A.; Chimaeze, Torty (International Journal of Contemporary Pediatrics, 2017)
Background: Epilepsies are the most common conditions encountered in most paediatric neurology clinics in many parts of the developing world. In sub-Saharan Africa epilepsies are secondary, reflecting persistently high risks at birth, and the adverse neurological sequelae of CNS infections during and beyond childhood. The study was designed to determine the clinical pattern of childhood epilepsies, probable aetiologies and associated comorbidities of the disease children. Methods: The study was conducted within an 18 months period among children having established epilepsy attending the Neurology Clinic of University of Calabar Teaching Hospital (UCTH). The children and or care givers were interviewed by the authors and the following data were obtained and recorded in a questionnaire; bio data, age at onset of seizure. History was obtained to determine the possible cause of the seizure, type of epilepsy and associated comorbidities. The data obtained was analysed with SPSS version 20. P-value <0.05 was considered significant. Results: Of the one hundred eighty children seen with various neurological morbidities during the study period, one hundred and seven had epilepsy which constitutes 59.4%. Generalized tonic clonic epilepsy was the commonest type of epilepsy found in 66 (61.1%) of the children with epilepsy, followed by simple partial and myoclonic epilepsy in 18.5% and 6.5% respectively. Severe birth asphyxia was responsible was the commonest identifiable cause of epilepsy in 19 (17.8%) of cases while central nervous system infection accounted for 14 (13.1%). Cerebral palsy was the commonest comorbidity in 20 (18.6%) followed by mental retardation in 17 (15.9%) of the children. Conclusions: The study showed epilepsy to be the commonest neurological presentation among children presenting at the paediatric neurology clinic of our facility. Primary generalised tonic clonic epilepsy was the commonest type of epilepsy seen, followed by simple partial seizures. Cerebral palsy and mental retardation were the main associated comorbidities. Birth injuries mainly severe birth asphyxia and CNS infection were the major causes of epilepsy in our study. In conclusion, epilepsy is the commonest neurological morbidity in our environment, limited facilities and resources still militate against identifying the actual aetiology in most children with the disease. Effort should be intensifying to eradicate the preventable causes of the disease.